Lipid exchanges between dioctadecyldimethylammonium bromide monolayer and vesicles in the subphase - Feitosa, Eloi; Adati, Renata D.; Constantino, Carlos J. L. [UNESP]; Aoki, Pedro H. B. [UNESP] (Wiley, 2022)
Studies on the interaction of lipid monolayer with bilayer structures, such as vesicles, are relatively scarce in the literature. In order to ascertain whether these structures interact for cationic dioctadecyldimethylammonium bromide (DODAB) monolayers at the aqueous surfaces of 0, 0.05, and 0.5 mmol L−1 DODAB vesicle dispersions, differential scanning calorimetry (DSC) and surface film balance experiments were carried out. DSC results confirmed the presence of unilamellar vesicles in the subphase, while changes in the monolayer surface pressure–area per molecule (π–A) isotherm profile yielded by the presence of DODAB vesicle in the subphase revealed monolayer-vesicle interactions as a result of monomer exchanges between the monolayer and the vesicles with stronger effects at the higher vesicle concentration investigated.
Keywords: DODAB; lipid monolayer; lipid vesicle; monolayer-vesicle interactions; monomer exchange